Asthma control limitations in selected primary health care clinics - Jesslee M. du Plessis; Jan J. Gerber (AOSIS, 2009)
Primary health care services worldwide are currently experiencing many quality-related problems. Efforts to improve these services appear to be sporadic and unsatisfactory. Investigations have revealed (Sharma & Sharma 2007) that one of the main causes for this state of affairs can be identif ed as neglected or inadequate documentation of patient/case history. The health care provider (HCP) should be equipped to improve the quality of health care and to take the lead in assuaging the predicament. The present study was undertaken to assess the correlation between asthma control and patient-related case history notes as recorded via the HCP. The data were obtained retrospectively from the patient notes of all asthmatic patients (including children and pregnant women) who attended six selected clinics in the North West Province of South Africa (Dr Kenneth Kaunda Municipal District). The analysis of the data collected from the patient clinic books confirmed the suspicion of poor quality of documentation, although the documentation in certain categories rendered some positive results. When compared to the GINA® guidelines, none of the patients had been controlled properly and only a small number (18.4%) had been controlled partly (GINA 2008). Asthma control may be enhanced when a standard template is developed for completion by the HCP. It is envisaged that this will ensure that vital information regarding asthma control is documented in order to contribute to satisfactory chronic disease control. Opsomming Primêre gesondheidsorgdienste wêreldwyd ondervind tans menige gehaltediens-verwante probleme, terwyl pogings om dit te verbeter sporadies en onbevredigend voorkom. Navorsing toon (Sharma & Sharma, 2007) dat een van die hoofoorsake hiervan die onvoldoende dokumentasie van die pasiënt of die geval se geskiedenis of nalating om te dokumenteer, is. Die gesondheidsorgverskaffer (GSV) moet toegerus word om die gehalte van gesondheidsorg te verbeter en leiding te neem om die verknorsing te hanteer. Hierdie studie het die korrelasie tussen asmabeheer en pasiëntgeskiedenis, soos genoteer deur 'n GSV, ondersoek. Dié data is retrospektief van die klinieknotas van alle asmapasiënte (kinders en swanger vroue ingesluit) verkry wat die ses klinieke in Noordwes Provinsie, Suid-Afrika (Dr. Kenneth Kaunda Munisipale Distrik), besoek het. Die analise van die data wat uit pasiënte se kliniekboekies versamel is, het die vermoede oor die swak gehalte van dokumentasie bevestig, alhoewel daar positiewe uitkomste was in sekere kategorieë se dokumentasie. Wanneer die dokumentasie met die GINA®-riglyne vergelyk word, is dit duidelik dat geen van die pasiënte optimaal bestuur is nie en slegs 'n klein groepie (18.4%) gedeeltelik bestuur is (GINA 2008). Asmabeheer sou kon verbeter deur 'n standaard templaat te ontwikkel wat die GSV kan voltooi. Daar word voorsien dat dit die dokumentering van die nodige inligting oor asmabeheer sal verseker en sodoende kan bydra tot die bevredigende bestuur van kroniese siektes.